2009
DOI: 10.1111/j.1365-2133.2009.09274.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies associated with dermatomyositis and polymyositis in Taiwan: a nationwide population-based study

Abstract: This is the first large-scale study to report the associated malignancies and the cancer risk of IIM in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 31 publications
6
83
1
1
Order By: Relevance
“…Malignancy was found after the diagnosis of DM in only 1 patient. This contrasts somewhat with previous studies 32,33 reporting that the diagnosis of DM is made before the development of malignancy in at least half of patients. Regarding patients with anti-155/140 Abs, Chinoy et al 34 reported that malignancy preceded the onset of DM in only 1 of 8 patients.…”
Section: Commentcontrasting
confidence: 96%
“…Malignancy was found after the diagnosis of DM in only 1 patient. This contrasts somewhat with previous studies 32,33 reporting that the diagnosis of DM is made before the development of malignancy in at least half of patients. Regarding patients with anti-155/140 Abs, Chinoy et al 34 reported that malignancy preceded the onset of DM in only 1 of 8 patients.…”
Section: Commentcontrasting
confidence: 96%
“…In studies carried out in Western countries, Hill et al [15], Sigurgeirsson et al [2] and others reported lung, colon and rectum cancer to be the most frequent malignancies. Chen et al reported that nasopharyngeal carcinoma, one of the most common neoplasmas in the Taiwanese population, was also the most frequent among Taiwanese patients with inflammatory myopathies [16][17][18]. These results suggest that the type and site of malignancy in patients with inflammatory myopathies parallels the expected probability of that cancer in each ethnic or regional population.…”
Section: Discussionmentioning
confidence: 92%
“…7,9,20 Patients with anti-MDA5-positive-DM have a malignancy risk similar to the general dermatomyositis population (3-6 fold increased risk compared to the general population), and thus should undergo age-appropriate workup for malignancy, including screening for nasopharyngeal carcinoma in patients of Asian descent. 7,14,[21][22][23][24] Treatment of anti-MDA5-positive-DM consists of potent immunosuppressive therapy, especially in the presence of underlying rapidly progressive ILD. 14 This patient had an unusual presentation of dermatomyositis, and several diagnostic errors contributed to a delay in his diagnosis (Table 2).…”
Section: Discussionmentioning
confidence: 99%